What to Expect in Primigravidae Adolescent Pregnancy with Malaria in Remote Area: A Case Report - Christian Murtani; Fiona Valerie Muskananfola; Jeffren Evander Bulan (Andalas Obstetrics And Gynecology Journal, 2024)
Background: Malaria is an infection transmitted by parasite-infected Anopheles mosquito. Pregnancy is one of the risk factors for infection and worse prognosisCase: Here we present a case of primigravidae adolescent pregnancy with malaria in a remote area. Patient presented with fever 10 days prior. Laboratory work-up showed microcytic hypochromic anemia, grade III thrombocytopenia, positive P. falciparum, and IUFD as disease outcome. The most common malaria-related hematological consequences are anemia and thrombocytopenia. Anemia in malaria is caused by the obligatory destruction of erythrocytes during the acute phase and might be related to bone marrow dyserythropoiesis. Several theories suggest mechanisms of thrombocytopenia in P. falciparum malaria such as increased platelet aggregation, bone marrow alteration, microvascular sequestration, and endothelial activation. Intrauterine Fetal Death (IUFD) might be related to microvasculature blockage or inflammation by the infected erythrocyte (IE). Inflammation in the intervillous regions of the placenta results in placental malaria (PM). PM may cause intrauterine growth restriction, premature delivery, and low birth weight, thus increasing newborn mortality.Conclusion: Malaria in pregnancy has a devastating impact on both mother and fetus. Patient’s characteristics and background greatly influence malaria outcomes and treatment continuity. Holistic treatment is recommended to enhance patient prognosis and health-seeking behavior